Of All the Mothers at Stake: Ecofeminism and Bangladeshi Films - Urmy, Khadizatul Kubra (Spectrum, 2023)
Ecofeminism explores the connection between nature and women, and the abusive treatment of both in the hands of patriarchy and the capitalistic modes of production. Essential feminists believe nature and women to be connected through their roles since the inception of earth and human civilization. The way mother nature provides human beings and animals with all the essentials to be born, grow up, and survive, and lets [1] the human civilization to flourish is similar to a woman’s giving birth to babies, and raising them with utmost care in the role of a mother. From that viewpoint, both nature and women are the origins and protectors of life. Therefore, exploiting the source of life itself indicates the [2] endangerment of life on earth. On the other hand, socialist ecofeminists believe that patriarchy uses this concept of the link between women and nature on the basis of the roles mentioned above only to dominate them. Bangladeshi filmmakers of this generation have become conscious of visually representing this age-old concept of woman-nature relationship – the abuse of both [3] in their films which can be analysed from an ecofeminist point of view. This paper explores two Bangladeshi films, Haldaa, directed by Tauquir Ahmed, and Padmapuran, directed by Rashid Polash, and sheds some light on the depiction of interconnectedness of nature and women from an essentialist ecofeminist perspective, and the subordination of both from a socialist ecofeminist perspective. It shows how human civilization will suffer if both nature and women, especially the mothers, are not treated and valued properly. Spectrum, Volume 17, June 2022: 75-88